Differential recovery of Streptococcus mutans from various mitis-salivarius agar preparations. - Liljemark, W F (1976)
Recoveries of Streptococcus mutans from human dental plaque were lower when plated on mitis-salivarius agar obtained from Baltimore Biological Laboratories as compared with mitis-salivarius agar obtained from Difco Laboratories. However, no difference in recoveries of established laboratory strains of S. mutans was observed between these two agar preparations.